2007
DOI: 10.1016/j.cardiores.2007.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Local adipose tissue depots as cardiovascular risk factors

Abstract: Obesity is associated with increased cardiovascular morbidity and mortality. Although obesity-associated hypertension, dyslipidemia and insulin resistance account in part for this association, it becomes increasingly apparent that a systemic and local pro-inflammatory response of adipose tissue might also be a contributing factor. White adipose tissue (WAT) is a highly active organ secreting various peptides such as cytokines, chemokines and hormone-like proteins. Besides the visceral and subcutaneous depots, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
1
17

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(117 citation statements)
references
References 115 publications
(121 reference statements)
2
97
1
17
Order By: Relevance
“…There have been a few reports on cytokines in epicardial adipose tissue. 5,[18][19][20][21][22][23] Iacobellis, et al reported that mRNA expression of adiponectin in epicardial adipose tissue was significantly lower in subjects with severe CAD than in those without CAD. 21) Our data suggest that enhanced infiltration of inflammatory cells into EAT may account for inflammatory cytokine expression in EAT of CAD patients, although our sample size was too small to draw a definitive conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few reports on cytokines in epicardial adipose tissue. 5,[18][19][20][21][22][23] Iacobellis, et al reported that mRNA expression of adiponectin in epicardial adipose tissue was significantly lower in subjects with severe CAD than in those without CAD. 21) Our data suggest that enhanced infiltration of inflammatory cells into EAT may account for inflammatory cytokine expression in EAT of CAD patients, although our sample size was too small to draw a definitive conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…52 Increased epicardial fat pads associated with intramyocardial lipid deposition may lead to both systolic and diastolic dysfunctions, whereas accumulation of fat around blood vessels (perivascular fat) may affect vascular function in a paracrine manner, as perivascular fat cells secrete vascular relaxing factors, proatherogenic cytokines and smooth muscle cell growth factors. 54,55 High amounts of perivascular fat could also mechanically contribute to the increased vascular stiffness observed in obesity, whereas accumulation of fat within the renal sinus associated with the increased intraabdominal pressure of visceral obesity may compress the renal papilla, the renal vein and lymphatics vessels, altering intrarenal physical forces that favor sodium reabsorption and arterial hypertension. 52 Finally, the accumulation of adipose tissue surrounding skeletal muscle bundles, that is, intermuscular adipose tissue (IMAT), albeit in the thigh region, also has a strong association with insulin resistance.…”
Section: Ectopic Fatmentioning
confidence: 99%
“…Adipocytes expand during normal aging, promoting visceral obesity and dysfunctional elevations of circulating AngII (Pacholczyk et al 2013). Chronic increases in AngII production mechanically damage the vascular wall (Zieman et al 2005), resulting in arterial stiffness and blood pressure variability (Thalmann and Meier 2007;Natale et al 2009). Arterial stiffness and elevated body mass are both significant predictors of white matter abnormalities and risk for ischemic stroke in older individuals (Safar et al 2000;Kuo et al 2010;Strazzullo et al 2010;Verstynen et al 2012), suggesting that abnormal activation of the peripheral RAS may influence cerebrovascular mechanisms of age-related white matter degeneration.…”
Section: Introductionmentioning
confidence: 99%